1968
DOI: 10.1128/aem.16.4.636-640.1968
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and Sensitive Detection of Bacteria by Gas Chromatography

Abstract: A gas chromatograph fitted with electron capture and flame ionization detectors was employed for the rapid detection of bacteria by analysis for their metabolic products. The presence of Proteus vulgaris, Streptococcus faecalis, S. liquefaciens, Escherichia coli B, Bacillus cereus, and B. popilliae was detected in 2 to 4 hr in media inoculated with less than 104 cells per ml, whereas a 7to 12-hr growth period was required for the detection of products formed in cultures of Serratia marcescens, Aerobacter aerog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
1

Year Published

1969
1969
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 2 publications
(2 reference statements)
0
6
1
Order By: Relevance
“…Gas chromatographic conditions were essentially the same as described previously by Mitruka and Alexander (8). The operating temperatures were 110, 175, and 190 C for the column, detector, and injector, respectively.…”
Section: Materiais and Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gas chromatographic conditions were essentially the same as described previously by Mitruka and Alexander (8). The operating temperatures were 110, 175, and 190 C for the column, detector, and injector, respectively.…”
Section: Materiais and Methodsmentioning
confidence: 99%
“…Gas chromatography has been used for differentiation of microorganisms growing in vitro (3, 4,12,13). In previous studies, we have reported on the application of gas chromatographic techniques for the rapid and sensitive detection of viable bacteria and viruses (8,9). The electron capture detector, in particular, was found to be extremely sensitive for the detection of several microbial metabolites (7).…”
mentioning
confidence: 99%
“…Solutions containing authentic chemical compounds and samples of the water and of the inoculated media were treated in an identical manner. The instrument and conditions for gas chromatography were essentially those employed previously (4,8). A 3.0-,liter sample containing the test substance was injected into the instrument, each detector thereby receiving 1.5 jliters.…”
Section: Methodsmentioning
confidence: 99%
“…Gas chromatographic techniques have been proposed for the rapid and sensitive detection of bacteria in view of the fact that certain common microbial metabolites can be detected in the nanogram and occasionally even in the picogram range with an electron capture detector (ECD) fitted on a chromatograph (7). Thus, the metabolites resulting from the activity of a few cells of certain species can be observed (8). Such procedures, however, fail to sense the products generated by low cell densities of other species, presumably because the metabolites excreted are not present in sufficiently high concentration or are not of the type sensitively detected by ECD.…”
mentioning
confidence: 99%
“…A 3.0-,uliter sample was injected into the gas chromatograph. The chromatographic techniques were essentially the same as described previously (2).…”
mentioning
confidence: 99%